The INFLUENCE OF NUTRITION ON DISEASE SEVERITY AND HEALTH-RELATED QUALITY OF LIFE IN ADULTS WITH SICKLE CELL DISEASE - Sanaa Kamal; Moheyeldeen Mohamed Naghib; Jamaan Al Zahrani; Huda Hassan; Karim Abdel Aziz Moawado; Omar Arrahman (Mediterranean Journal of Hematology and Infectious Diseases)
Background & Aims: Sickle cell disease (SCD has a worldwide distribution and causes significant morbidity and mortality in children and adults. Few studies addressed the determinants of SCD severity in adults; therefore, we investigated the impact of nutrition on the outcome of SCD and health-related quality of life (HRQoL) in adult patients,